PENERAPAN BALANCED SCORECARD SEBAGAI ALAT UKUR PENILAIAN KINERJA PERUSAHAAN (STUDI KASUS PADA PDAM TIRTA DAROY BANDA ACEH) - Syah, Fadiel Muhammad; Suparno, Suparno (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aims to look at how the company PDAM Tirta Daroy as Regional Owned Enterprises (enterprises) are enabled to provide services and the provision and management of water in the city of Banda Aceh using the Balance Scorecard. Intended use of the Balanced Scorecard method is to measure the performance of companies based on four perspectives: Financial Perspective, Internal Business Process Perspective, Customer Perspective, and Perspective Growth and Learning. As long as the company has only used performance measurement based on financial and operational aspects only. The data used in this research is secondary data and primary data. Secondary data is data obtained documentation from the company. Primary data obtained from the results of the questionnaire Spread to customer satisfaction and employee satisfaction, and interviews with management. From the results of measurements that have been made known that the performance of PDAM Tirta Daroy overall is quite good, it is shown by the value Scorecard resulting from any perspective. From the results of measurements that have been made known that the performance of PDAM Tirta Daroy overall is quite good, it is shown by the value Scorecard resulting from any perspective. Accurate performance measurement results are very important for management, both at the planning, decision-making and control, as well as in realizing the vision and mission of the company